2021
DOI: 10.1002/pbc.29454
|View full text |Cite
|
Sign up to set email alerts
|

Postchemotherapy tumor volume as a prognostic indicator in Wilms tumor: A single‐center experience from South India

Abstract: Background: Optimal risk stratification is the key to minimizing relapse and toxicity in children with Wilms tumor (WT). The study evaluated poor tumor volume response to chemotherapy as a risk factor that predicts relapse. Procedure: Children with WT who were treated between 2005 and 2020 at the center were analyzed. Tumor volumes at the time of diagnosis and after preoperative chemotherapy were calculated from cross-sectional imaging. The International Society of Paediatric Oncology (SIOP)-WT-2001 protocol w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…12,14 Delayed presentation with advanced localized and/or metastatic disease, malnutrition, incomplete staging workup, suboptimal surgical and histopathological expertise, malnutrition, inadequate supportive care facilities, treatment abandonment, and scarcity of collaborative research has been identified as critical barriers to achieving better survival outcomes in LMICs. [15][16][17] This study illustrates the disparities in pre-referral management and its impact on survival outcomes, in comparison to the patients who were treated with F I G U R E 3 Continued pre-operative chemotherapy followed by nephrectomy performed at a large pediatric oncology unit in an LMIC.…”
Section: Discussionmentioning
confidence: 94%
“…12,14 Delayed presentation with advanced localized and/or metastatic disease, malnutrition, incomplete staging workup, suboptimal surgical and histopathological expertise, malnutrition, inadequate supportive care facilities, treatment abandonment, and scarcity of collaborative research has been identified as critical barriers to achieving better survival outcomes in LMICs. [15][16][17] This study illustrates the disparities in pre-referral management and its impact on survival outcomes, in comparison to the patients who were treated with F I G U R E 3 Continued pre-operative chemotherapy followed by nephrectomy performed at a large pediatric oncology unit in an LMIC.…”
Section: Discussionmentioning
confidence: 94%
“…Tumor volume is associated with the proliferation and malignancy of tumor cells and, in clinical practice, is an important factor affecting the survival of patients and prognosis [22][23][24][25]. However, the evaluation of PA cell proliferation based on PA volume cannot account for the effect of hemorrhage or necrosis on the growth of PAs.…”
Section: Discussionmentioning
confidence: 99%
“…By applying a specific network structure, accurate manual results can be achieved. However, extensive training can automate this process [ 11 ]. Many scholars have conducted research on deep learning, recognizing its potential for automatically segmenting lesions and saving time while minimizing subjective errors.…”
Section: Introductionmentioning
confidence: 99%